The effect of rock permeability and porosity on seismoelectric conversion: experiment and analytical modelling. Issue 1 (3rd June 2019) - Peng, Rong; Di, Bangrang; Glover, Paul W J; Wei1, Jianxin; Lorinczi, Piroska; Ding, Pinbo; Liu, Zichun; Zhang, Yuangui; Wu, Mansheng
SUMMARY: The seismoelectric method is a modification of conventional seismic measurements which involves the conversion of an incident poroelastic wave to an electromagnetic signal that can be measured at the surface or down a borehole. This technique has the potential to probe the physical properties of the rocks at depth. The problem is that we currently know very little about the parameters which control seismoelectric conversion and their dependence on frequency and permeability, which limits the development of the seismoelectric method. The seismoelectric coupling coefficient indicates the strength of seismoelectric conversion. In our study, we focus on the effects of the reservoir permeability, porosity and frequency on the seismoelectric coupling coefficient through both experimental and numerical modellings. An experimental apparatus was designed to record the seismoelectric signals induced in water-saturated samples in the frequency range from 1 to 500 kHz. The apparatus was used to measure seismoelectric coupling coefficient as a function of porosity and permeability. The results were interpreted using a microcapillary model for the porous medium to describe the seismoelectric coupling. The relationship between seismoelectric coupling coefficients and the permeability and porosity of samples were also examined theoretically. The combined experimental measurements and theoretical analysis of the seismoelectric conversion has allowed us to ascertain the effect of increasing porosity and permeability on the seismoelectric coefficient. We found a general agreement between the theoretical curves and the test data, indicating that seismoelectric conversion is enhanced by increases in porosity over a range of different frequencies. However, seismoelectric conversion has a complex relationship with rock permeability, which changes with frequency. For the low-permeability rock samples (0–100 × 10 −15 m 2 ), seismoelectric coupling strengthens with the increase of permeability logarithmically in the low-frequency range (0–10 kHz); in the high-frequency range (10–500 kHz), the seismoelectric coupling is at first enhanced, with small increases of permeability leading to small increases in size in electric coupling. However, continued increases of permeability then lead to a slight decrease in size and image conversion again. For the high-permeability rock samples (300 × 10 −15 –2200 × 10 −15 m 2 ), the seismoelectric conversion shows the same variation trend with low-permeability samples in low-frequency range; but it monotonically decreases with permeability in the high-frequency range. The experimental and theoretical results also indicate that seismoelectric conversion seems to be more sensitive to the changes of low-permeability samples. This observation suggests that seismic conversion may have advantages in characterizing low permeability reservoirs such as tight gas and tight oil and shale gas reservoirs.